Brief atlas of the human body - Patton, Kevin T. 4 0 16; 1938- Thibodeau, Gary A.; 5 (St. Louis, Mo. : Mosby/Elsevier, 2010)
A supplement to the seventh edition of the Mosby/Elsevier Anatomy & Physiology text,featuring over two hundred labeled illustrations of surface anatomy, the skeleton, internal anatomy, cross-sectional anatomy, and histology.
Adult;Adult
Keywords: 2 -- 0; 6; Human physiology.;Human anatomy.;Physiology.;Human anatomy; 20; 2